Analysis of profiles of patients on oral anticoagulants undergoing dental extraction - A retrospective study - Daroit, Natália Batista; Festugatto, Fábio Luis; Beltrame, Luiz Felipe; Maciel, Júlio César Córdova; Rados, Pantelis Varvaki (Journal of Oral Diagnosis, 2017)
Introduction: Many oral surgeons, in clinical practice, face the challenge of management of patients under anticoagulants treatment. The main reason for this concern is the post- operative problems. Objective: The objective is to demonstrate the profiles of patients on oral anticoagulants, who underwent exodontia and did not have complications. Material and Methods: This review was performed using the records of all cases of Special Care Dental Ambulatory during a period of two years. Results: Records of a total of 60 patients, 82 procedures, and 145 extracted teeth were found. The anticoagulant utilized for the sample was warfarin, the mean INR was 2.47 (SD ± 0.53), the majority of teeth extracted was monoradicular was extracted one/time. Conclusion: Can be inferred that is safe to perform dento-alveolar surgeries in anticoagulants patients since additional care measures such as INR monitoring, minimally traumatic technique, and local hemostasis are adopted. This research clarifies some aspects related to routinely surgical procedures in patients under oral anticoagulant therapy.